Cryopreservation for Cell Banking: Current Concepts at the Turn of the 21st Century - Fuller, B.; Green, C.; Grischenko, V. I. (Problems of Cryobiology and Cryomedicine, 2006)
It is only just over 50 years since the first reports of recovery of living cells from cryogenic temperatures, but since then, the science of cryobiology has progressed to make an impact in many areas of biology and medicine. Cryopreservation has become a central, routine procedure in areas such as human reproductive medicine, animal breeding, banking of cells from many genera (both prokaryotes and eukaryotes) to establish Reference Collections, and cryo-banking of blood and small tissues. During this time, a considerable understanding has been accrued of the basic mechanisms which control cell death or survival, and the aims of the current review are to set out this information. There also remain many challenges ahead, to expand the science of cryobiology in biotechnology and tissue engineering, and these are discussed.